The Influence of Independent Board of Commissioners, Audit Committee and Leverage on Tax Avoidance in Health Sector Companies Listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 Period - Kawengian, Klarisa; J. Sondakh, Jullie; R. N. Wokas, Heince (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Tax is one of the main sources of national income in Indonesia, playing a crucial role in supporting the country's finances and development. For companies, tax is considered a financial burden that can reduce profits. Therefore, companies tend to engage in legal tax planning, known as tax avoidance, to reduce the tax burden. This study aims to examine the influence of independent board of directors, audit committee, and leverage on tax avoidance in healthcare sector companies listed on the Indonesia Stock Exchange during the period 2018-2022. The sampling method used is purposive sampling, resulting in 12 companies out of a total of 33 companies in the population. The analysis was conducted using multiple linear regression with the assistance of IBM SPSS version 29. The results show that leverage has an effect on tax avoidance, while independent board of directors and audit committee do not affect tax avoidance.